A simple cartilage sparing “Madhumani technique” of endoscopic septoplasty - Rao, C. Madhusudana; Manideep, C.; Rohith, C. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Deviated nasal septum is commonest cause of nasal obstruction, noisy breathing, sinusitis, sleep disturbance, headache, etc. Endoscopic septoplasty gives better results and better relief to the patients than age old procedure like submucosal resection (SMR). In our study, a total of 317 patients who were undergoing septoplasty and turbinectomy were included over the period of 3 years. 143 patients were female and 174 patients were male. All presented with complaints of breathing difficulty and nasal block. All cases were done by following our protocol of pre-op and post op care. Patients were followed up with 4 post op visits over a period of 6 months. All patients had symptomatic relief by 2 weeks post operatively. No major complications were encountered per operative and post operative. Minor complications like asymptomatic adhesions seen in very few patients which were released during the follow up visit. None of the patient needed revision surgery. This paper describes the simple enoscopic septoplasty technique followed by us in our institute. With our experience we framed simple, easy protocol of cartilage sparing “madhumani technique’’ of endoscopic septoplasty which can be easily followed and good results can be achieved by using septal splints as necessary.